Nurses' views and applications on palliative care. Issue 3 (30th November 2020) - Lafci, Diğdem; Yildiz, Ebru; Pehlivan, Seda
Abstract: Purpose: This study was carried out descriptively to determine the view and applications about pallative care of nurses working in a university hospital. Design and Methods: The data were collected with the questionnaire form: "Individual Information Form" and "Views and Appllications on Palliative Care, " created by the researchers in line with the literature. Findings: A total of 96.6% of the nurses evaluated the scope of palliative care as pain relief, and the most common difficulties in care were identified as bad news (88.1%). In all, 22.0% of the nurses talked to the patient and their family about death. Practice Implications: It is thought that the majority of nurses are not trained in palliative care and their opinions about palliative care are affected by this situation.